An Alanine-Rich Peptide Attenuates Quorum Sensing-Regulated Virulence and Biofilm Formation in Staphylococcus aureus. (23rd November 2019) - Al Akeel, Raid; Mateen, Ayesha; Syed, Rabbani
Abstract: Background: Alanine-rich proteins/peptides (ARP), with bioactivity of up to 20 amino acid residues, can be observed by the body easily during gastrointestinal digestion. Objective: Populus trichocarpa extract's capability to attenuate quorum sensing-regulated virulence and biofilm formation in Staphylococcus aureus is described. Methods: PT13, an ARP obtained from P. trichocarpa, was tested for its activity against S. aureus using the broth microdilution test; a crystal-violet biofilm assay was performed under a scanning electron microscope. The production of various virulence factors was estimated with PT13 treatment. Microarray gene expression profiling of PT13-treated S. aureus was conducted and compared with an untreated control. Exopolysaccharides (EPS) was estimated to observe the PT13 inhibition activity. Results: PT13 was antimicrobial toward S. aureus at different concentrations and showed a similar growth rate in the presence and absence of PT13 at concentrations ≤8 μg/mL. Biofilm production was interrupted even at low concentrations, and biofilm-related genes were down-regulated when exposed to PT13. The genes encoding cell adhesion and bacterial attachment protein were the major genes suppressed by PT13. In addition, hemolysins, clumping activity, and EPS production of S. aureus decreased after treatment in a concentration-dependent manner. Conclusions: A long-chain PT13 with effective actions that, even at low concentration levels, not only regulated the gene expression in the producer organism but also blocked the virulence gene expression in this Gram-positive human pathogen is described. Highlights: We identified a PT13 as a potential antivirulence agent that regulated production of bacterial virulence determinants (e.g., toxins, enzymes and biofilm), downwards and it may be a promising anti-virulence agent to be further developed as an anti-infective agent.